الحركة العلمية في الدولة الرستمية 160 - 296 هـ/ 777 - 909 م - راشد, ريم محمود محمد (مجلة البيان العلمية المحكمة, 2025)
Keywords: Dynastie rustumide; Vie intellectuelle -- Rustumides

‏ملامح الحياة الثقافية والسياسية في الدولة الرستمية 160-296هـ/776-909م - الشيخ بالحاج, قاسم بن أحمد (دار امل, 2021)
Keywords: Vie intellectuelle -- Rustumides

Non-caliphal Rulers and Their Writings in the Islamic West (2nd–9th/8th–15th Centuries) - Fierro, Maribel (Rulers as Authors in the Islamic World, 2024)
Among the dynasties ruling in the Islamic West, the Idrisids, the Aghlabids, the Fatimids, the Zirids and the Andalusi Taifa kings wrote poetry, but not the Ibāḍī rulers from North Africa. In the Ibāḍī and Ṣufrī polities that were established in Berber-speaking contexts court poetry in Arabic seems to have been absent, while religious piety and learning were extolled. In other contexts, the ability to write poetry signalled a ruler’s distinction, acumen and knowledge. Such ability seems to have been taken for granted in the case of the Cordoban Umayyad emirs and later among the Taifa kings, except for those who were Ṣaqāliba (slaves of European origin). The Arab Taifa king of Seville al-Muʿtamid (r. 461–484/1068–1091) was a highly talented poet whose verses are still appreciated and studied today. The existence of Andalusi rulers who wrote poetry was one of the elements that certain Andalusi authors emphasized in order to prove the cultural superiority of ‘Arab’ al-Andalus over North African ‘Berberdom’, although some members of both the Almoravid and Almohad dynasties are mentioned as having written poetry in Arabic. Rulers in the Islamic West also wrote prose works dealing with the art of government, the loss of power, adab, geometry, bookbinding and astronomy, a variety of topics that is to be understood in each specific context as explained in the second section of this chapter. Finally, the case of authors who became rulers is analyzed: the poet Ibn ʿAmmār, the ʿAzafids of Ceuta, the mystics Ibn Qasī (d. 546/1151) and Ibn Aḥlā al-Anṣārī (d. 645/1247), and the Mahdī Ibn Tūmart (d. 524/1130).
Keywords: Vie intellectuelle -- Rustumides